Episiorrafia en primíparas y su relación con la función sexual en usuarias del Centro de Salud Nro. 1, Loja - Cuenca Vega, María Fernanda (2015)
It executed this investigation to determine the relation between the episiotomy in primiparous women and the sexual function; determine the incidence of sexual dysfunction in primiparous users with episiotomy; Establish the dysfunction in primiparous with episiotomy in relation with the chronological age; establish the sexual function in relation with the complications of the episiotomy.- This analysed 60 surveys in patients with antecedents of the episiotomy in puerperium.- It applied a questionnaire self- abminister for the obtaining of the chronological age and questions for the identification of the criteria of inclusion and exclusion; Later a Test Sexual Function of the Woman, that allowed the evaluation of the evaluators assessing sexual function domains. The variables studied were episiotomy, primiparous women, puerperium and sexual function. This investigation was of quantitative type, descriptive and retrospective. The results showed the existence of sexual dysfunction in a greater percentage of 20% of the patient, with affectation of the disorder of the wish – excitation (28,3%). The disorders of the sexual cycle presented in 44,4% of patients between the ages of 15 to 19 years, the disorder with greater affectation was the wish -excitation (55,6%); 43,3% of the patients presented complications of episiotomy, the main complication was the infection with 25% and related with the disorders of penetration and anxiety (37,5%).- It concludes that the sexual function in all the evaluators commands of the phases of the cycle see negatively affected by the realisation of episiotomy during the childbirth of the primiparous women. Keywords: Episiotomy, Primiparous Women, Sexual Function